THE POPULATION DYNAMICS IN THE RUSSIAN ARCTIC - D. Rudenko (Модернизация, инновация, развитие)
The paper proves the necessity to invest into the human capital in order to be settled in the Arctic and to compete for the resources there. TheArctic zone is characterized by depopulation. The fi xed eff ect model of population growth in 8 Russian Arctic regions from 1997 to 2013 indicates that poverty, number of doctors, education opportunities, housing availability have substantial eff ects. Eliminating excessive spatial diff erences in the social development of Arctic regions should be seen as a priority of the state policy in the Arctic in order to make it attractive for living.